Kebijakan Cukai Konsumsi Minuman Berpemanis dalam Kemasan (MBDK) dalam Mengendalikan Masalah Kesehatan: Tinjauan Literatur Sistematis dan Meta Analisis - Hartono, Risky Kusuma; Aryani Susanti, Fitria (Jurnal Ekonomi Kesehatan Indonesia, 2025)
Globally, the consumption of sugar-sweetened beverages (SSBs) has increased by nearly 16%. The imposition of taxes on sugary drinks is considered one of the strategic measures to control diseases associated with their consumption. This study aims to conduct a meta-analysis of the correlation between SSB taxation and health issues. The systematic review and meta-analysis were carried out following the Preferred Reporting Items for Systematic Reviews and MetaAnalyses (PRISMA) guidelines. Literature from various countries published since January 1, 2014, was collected using databases such as Google Scholar, PubMed, and Science Direct. The meta-analysis process was performed using a funnel plot. A total of 44 articles meeting the criteria and relevance were selected for the meta-analysis. The highest implementation rate of SSB taxation was 60%, while the lowest was 7%, with an average tax rate of 20% across 20 states. The results of the meta-analysis demonstrated a significant positive relationship between SSB taxation and the prevalence of overweight (0.17, 95% CI: 0.09 to 0.25), obesity (0.23, 95% CI: 0.10 to 0.35), diabetes (0.16, 95% CI: 0.01 to 0.31), cancer (0.12, 95% CI: -0.06 to 0.28), heart disease (0.12, 95% CI: -0.03 to 0.26), and dental caries (0.37, 95% CI: -0.05 to 0.68). However, no significant association was found between SSB taxation and stroke prevalence (0.02, 95% CI: 0.01 to 0.04). This study highlights a significant positive association between the imposition of taxes on sugary beverages and the high prevalence of health problems such as overweight, obesity, diabetes, cancer, heart disease, and dental caries, while the relationship with stroke prevalence was insignificant. The study recommends policymakers formulate and enhance the effectiveness of SSB taxation policies.